(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
An abnormal ratio of triglycerides to HDL (TG/HDL) indicates an atherogenic lipid profile and a risk for the development of coronary disease. Dyslipidemia is one of the independent risk factors for atherosclerotic disease. We determined whether the LDL/HDL ratio is better than LDL or HDL alone in predicting the severity of atherosclerosis. The study was performed on 100 patients with myocardial ischemia who underwent coronary angiography between October 2023 and Feb. 2024 in the heart center in Najaf City. Our result showed that only TG/HDL-c and HDL-c were useful for detecting extensive atherosclerosis disease, with the former more strongly associated with the disease. Although some lipid variables were associated with the extent of atherosclerosis disease, the ratio of triglycerides to HDL-cholesterol showed the strongest association with the extent Higher LDL/HDL ratio was seen in CAHD patients than in controls (LDL/HDL ratio was significantly associated with the severity of coronary vascular stenosis.